ANALISIS PENGARUH KEPUASAN KERJA TERHADAP KINERJA GURU DENGAN KEPEMIMPINAN KEPALA SEKOLAH SEBAGAI VARIABEL MODERASI (Survei pada Guru PNS di SMP Negeri 1 Jumapolo) - Sutarno, Rika Dewi Saputri, Suprayitno & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
This study aims to analyze the effect of job satisfaction on the performance of teachers. The effect of leadership on teacher performance. The effect of job satisfaction on performance with less leadership as a moderating variable. The study population was all teachers civil servants in SMP Negeri 1 Jumapolo, with a sample of 40 respondents. Data collection technique used questionnaire that through stages of testing the validity and reliability. Data were analyzed using the validity test, reliability test, classic assumption test and test-gap absolute value. Based on the results of research in the know that job satisfaction does not significantly influence the performance of teachers. Leadership significant effect on the performance of teachers. Leadership moderating effect of job satisfaction on the performance of teachers.Keywords: job satisfaction, leadership, performance.